Macropinocytosis enhances foamy macrophage formation and cholesterol crystallization to activate NLRP3 inflammasome after spinal cord injury - Chenxi Zhang; Shujie Zhao; Zhenfei Huang; Ao Xue; Hao Liu; Siming Dai; Ziyang Zheng; Yin Li; Xiaodong Guo; Jun Gu; Feng Zhang; Fubing Wang; et al. (Redox Biology)
After spinal cord injury (SCI), phagocytes endocytose myelin debris to form foam cells, exacerbating the inflammatory response. It has been previously shown that macrophages become foam cells through the phagocytosis of myelin debris via receptor-dependent mechanisms after SCI. Blocking receptor-mediated endocytosis did not completely prevent foam cell formation, so we investigated receptor-independent endocytosis. Here, we revealed that foam cells formed after myelin debris internalization were predominantly macrophages rather than microglia. Receptor-independent macropinocytosis has an important position in foamy macrophage formation through engagement of myelin debris endocytosis after SCI. Mechanistic studies showed that cholesterol crystallization following macropinocytosis-mediated foamy macrophage formation promoted the reactive oxygen species (ROS) production and the NOD-like receptor protein 3 (NLRP3) inflammasome activation, increasing the secretion of interleukin-1β (IL-1β). Inhibition of macropinocytosis might reverse this effect, resulting in enhanced axonal regeneration and reduced neural apoptosis, thereby improving outcomes after SCI. Overall, our study revealed a previously unrecognized role for macropinocytosis in foamy macrophages formation after SCI, and confer a promising therapeutic strategy for SCI through focus on macropinocytosis.